Organisational Learning and Knowledge Sharing Culture in Township Schools: An Exploration of Effective and Ineffective Practices - Nkambule, Bongani Innocent (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2023)
Literature underscores that the Fourth Industrial Revolution (4IR) promises to bring with it a host of technical and socially oriented innovations and changes that will pressure educational institutions to incorporate the concept of knowledge management (KM) in their educational, human resource, curricular and co-curricular administrative functions. In light of the many challenges confronting township schools such as the lack of proper infrastructure, the lack of learning and technological equipment and insufficient budget, the primary objective of this qualitative study (involving a sample of 20 participants), was to draw parallels between the effective and ineffective knowledge sharing practices in three township schools in the city of Emalahleni in Mpumalanga Province, South Africa. The study found that of the three schools under study, only one school practiced effective knowledge sharing, while the other two schools were found to be ineffective in their practise of knowledge sharing. Thematic analysis indicated that, in both schools, ineffective knowledge sharing was precipitated by a counter collaborative culture, top down communication and decision making, absence of Ubuntu (i.e., humanity, tolerance and mutual respect) among staff, the principals’ inaccessibility to non-managerial staff, and chronic teacher absenteeism. Based on these findings, the study proposes that best practices from the school that was found to have practiced effective knowledge sharing be emulated throughout the landscape of township schools in South Africa.